Freeing the Modern Slaves, One Click at a Time: Theorising human trafficking, modern slavery, and technology - Milivojevic, Sanja; Moore, Heather; Segrave, Marie (Anti-Trafficking Review, 2020)
This paper analyses relations between human trafficking, modern slavery, and information communication technology. It looks at the history of the technology-trafficking nexus and flags some key advances in the counter-trafficking discourse in the last two decades. It provides an overview of how technology has been framed as both a part of the problem and part of the solution in the trafficking/slavery context and emphasises the impact of such developments on a range of actors, in particular, potential victims, NGOs, and the nation state. We suggest that the technology-slavery/trafficking connections, while often elusive, act as potent narrative and policy setters that can advance existing challenges and create new points of tension in the counter-trafficking context. We critically analyse these points of tension and destabilise some of their underpinning assumptions. In the conclusion, we highlight the need for rigorous empirical evidence, arguing that a more robust scholarly engagement with the role of technology in enabling and disrupting exploitation is essential. We also point to the importance of ensuring that technology is not a distraction from addressing the root causes of exploitation and abuse.